Karakteristik Naskah Terjemahan Al-Qur’an Pegon Koleksi Perpustakaan Masjid Agung Surakarta - Gusmian, Islah (SUHUF, 2012)
This article describes the characteristics of a manuscript containing a trans-lation of the Qur’an into Javanese Pegon script found in the collection of the library of the Great Mosque of Surakarta. The translation were composed as teaching material for use in the Madrasah Manba'ul-Ulum, an Islamic boarding school established with the support of the Surakarta Kraton and under the authority of His Majesty Sri Pakubuwono IX (1861-1893). The level of language used in the Pegon text is ordinary Javanese with the model for the translation being based on exegesis which is the critical explanaton or interpretation of a religious text. The manuscript is historical proof of the intimate relationship existing between Islam and the Kraton, as well as the palace’s role in the development of Islamic education, in Surakarta in the late of 19th century CE. The manuscript contributed to enriching pesantren learning which is more widely known for its traditions of scientific Islamic jurisprudence (fiqh) and Sufism at that time.